Strategi Peningkatan Kinerja Pegawai di Kantor Dinas Kependudukan dan Pencatatan Sipil Kabupaten Toraja Utara - Kristian Hoegh Pride Lambe; Eliyanto Palondongan; Petrus Ma’na; Asrin Tandi (Al-Buhuts, 2024)
This study aims to determine and analyze strategies for improving employee performance, supporting factors for improving employee performance and inhibiting factors for improving employee performance at the Population and Civil Registry Office of North Toraja Regency. This research is a type of qualitative research. The research took the object of research at the Office of Population and Civil Registration of North Toraja Regency. Data sources in this study come from primary data and secondary data. The data collection method is through observation, interviews and documentation. The data analysis method in this study uses an interactive analysis method, starting from data reduction, data presentation and data verification or conclusion drawing. The results showed that: The strategy in improving employee performance is carried out by providing direction and guidance for employees in carrying out their work and being given guidance so that they are able to do the work given to them in accordance with the Operational Standardization of Work (SOP) that applies within the scope of the Population and Civil Registry Office of North Toraja Regency. The inhibiting factors in improving employee performance include that there are still employees who live far from the office, so that employee delays in coming to work often occur, and there are still some employees who occupy positions and structures that are not in accordance with their competence, where the placement of these employees is only to fulfill the organizational structure. Supporting factors in improving employee performance are facilities and infrastructure in accordance with operational standardization of work (SOP), and in general the condition of the workspace is comfortable and clean, so that employees feel at home and happy when they are in the workspace